A scoping review of implementation considerations for harm reduction vending machines - Erin Russell; Jessica Johnson; Zach Kosinski; Callie Kaplan; Nicole Barnes; Sean Allen; Emily Haroz (BMC, 2023)
Abstract Background Community-based harm reduction vending machines (HRVM) are not new to the field of public health; numerous countries have implemented them in response to the needs of people who use drugs over the last three decades. However, until recently, few existed in the United States. Given the rapidity with which communities are standing up harm reduction vending machines, there is a pressing need for a consolidated examination of implementation evidence. This scoping review summarizes existing literature using multiple implementation science frameworks. Methods The scoping review was conducted in five stages including (1) Identify the research question; (2) Identify relevant studies; (3) Select the publications based on inclusion/exclusion criteria; (4) Review and extract data; and, (5) Summarize results. PubMed, Embase, and Web of Science were searched and authors screened publications in English from any year. Data were extracted by applying implementation constructs from RE-AIM and the Consolidated Framework for Implementation Research (CFIR). Both frameworks provided a useful lens through which to develop knowledge about the facilitators and barriers to HRVM implementation. The review is reported according to PRISMA guidelines. Results After applying the full inclusion and exclusion criteria, including the intervention of interest ("vending machines") and population of interest ("people who use drugs"), a total of 22 studies were included in the scoping review. None of the studies reported on race, making it difficult to retroactively apply a racial equity lens. Among those articles that examined effectiveness, the outcomes were mixed between clear effectiveness and inconclusive results. Evidence emerged, however, to address all CFIR constructs, and positive outcomes were observed from HRVM's after-hour availability and increased program reach. Recommendations HRVM implementation best practices include maximizing accessibility up to 24 h, 7 days a week, offering syringe disposal options, ensuring capability of data collection, and allowing for anonymity of use. Organizations that implement HRVM should establish strong feedback loops between them, their program participants, and the broader community upfront. Considerations for future research include rigorous study designs to evaluate effectiveness outcomes (e.g. reduced drug overdose deaths) and examination of HRVM reach among ethnic and racial communities.